Metabolic acidosis may be as protective as hypercapnic acidosis in an ex-vivo model of severe ventilator-induced lung injury: a pilot study - Kapetanakis, Theodoros (BioMed Central, 2011)
BACKGROUND: There is mounting experimental evidence that hypercapnic acidosis protects against lung injury. However, it is unclear if acidosis per se rather than hypercapnia is responsible for this beneficial effect. Therefore, we sought to evaluate the effects of hypercapnic (respiratory) versus normocapnic (metabolic) acidosis in an ex vivo model of ventilator-induced lung injury (VILI). METHODS: Sixty New Zealand white rabbit ventilated and perfused heart-lung preparations were used. Six study groups were evaluated. Respiratory acidosis (RA), metabolic acidosis (MA) and normocapnic-normoxic (Control - C) groups were randomized into high and low peak inspiratory pressures, respectively. Each preparation was ventilated for 1 hour according to a standardized ventilation protocol. Lung injury was evaluated by means of pulmonary edema formation (weight gain), changes in ultrafiltration coefficient, mean pulmonary artery pressure changes as well as histological alterations. RESULTS: HPC group gained significantly greater weight than HPMA, HPRA and all three LP groups (P = 0.024), while no difference was observed between HPMA and HPRA groups regarding weight gain. Neither group differ on ultrafiltration coefficient. HPMA group experienced greater increase in the mean pulmonary artery pressure at 20 min (P = 0.0276) and 40 min (P = 0.0012) compared with all other groups. Histology scores were significantly greater in HP vs. LP groups (p < 0.001). CONCLUSIONS: In our experimental VILI model both metabolic acidosis and hypercapnic acidosis attenuated VILI-induced pulmonary edema implying a mechanism other than possible synergistic effects of acidosis with CO2 for VILI attenuation.